Reappraisal of the F/M amplitude ratio in carpal tunnel syndrome - Ginanneschi, Federica (Funct Neurol, 2017)
The F-wave/M-wave amplitude (F/M-amp) ratio has been shown to be increased in peripheral neuropathies, provided the maximum M-wave is relatively preserved. Reduced M-wave amplitudes and central facilitation of antidromically-induced reactivation of the anterior horn cells’ axon hillocks (F-wave) are believed to contribute to higher F/M-amp ratios. The present study was undertaken to re-evaluate mechanisms responsible for higher F/M-amp ratios in carpal tunnel syndrome (CTS). We enrolled 232 cases affected by CTS and 108 controls. F-and M-wave amplitudes and F-wave chronodispersion were analyzed for the median and ulnar nerves. The F/M-amp ratio of the median nerve in CTS subjects with moderate-severe nerve damage was significantly higher than that of mild CTS subjects and controls. Chronodispersion of the median nerve F-wave increased with increasing CTS severity. We conclude that the relative preservation of the median nerve F-wave is due to damage to the large diameter muscle afferent fibers responsible for the monosynaptic response. Absence of the monosynaptic response makes the small motoneurons, usually inaccessible to the antidromic volley because of its collision with the orthodromic reflex volley, able to fire in the F-wave.